2015
DOI: 10.1038/srep12694
|View full text |Cite|
|
Sign up to set email alerts
|

Calcium ion-induced formation of β-sheet/-turn structure leading to alteration of osteogenic activity of bone morphogenetic protein-2

Abstract: Preserving bioactivity of bone morphogenetic protein 2 (BMP-2) still remains a challenge in protein-based therapy. It is not known how Ca2+ released from extracellular matrix or existing in physiological environment influences bioactivity in situ till now. Here, effects of extracellular Ca2+ on conformation and osteogenic bioactivity of recombinant human BMP-2 (rhBMP-2) were investigated systematically. In vitro results indicated that Ca2+ could bind rhBMP-2 rapidly and had no obvious effect on cell behaviors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…These data suggest that the CaSr-MOFs may release Ca and Sr from the matrix and with a cumulative effect on osteoinduction. These results are supported by previous studies performed with alloys of Mg-Ca-Sr, which suggested that Ca and Sr by themselves may lead to osteoinduction 8,9 .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These data suggest that the CaSr-MOFs may release Ca and Sr from the matrix and with a cumulative effect on osteoinduction. These results are supported by previous studies performed with alloys of Mg-Ca-Sr, which suggested that Ca and Sr by themselves may lead to osteoinduction 8,9 .…”
Section: Resultssupporting
confidence: 89%
“…The alloys were also able to upregulate several osteogenic genes such as RUNX2, OSX, and ALP 7 . Additionally, Zhang et al and Berglund et al demonstrated that the presence of Ca, Mg and Sr cations simultaneously can lead to bone regeneration 8,9 . Therefore, materials that can release Ca and Sr simultaneously for extended periods of time can provide osteogenic signals.…”
mentioning
confidence: 99%
“…Although it has been proved that a certain amount of surface chemical composition (e.g. Ca 2+ ) could affect proliferation and differentiation of MSCs (Hu et al, ; Shie, Chiang, Chen, Liu, & Chen, ; Zhang et al, ), the changes of surface chemical composition in different mineralized collagen groups in this study influenced the MSCs in aspects of proliferation and differentiation indistinctively and erratically. It may be due to the minor changes of chemical content among the different groups, which did not reach the effective dose.…”
Section: Discussionmentioning
confidence: 55%
“…Smad3 and Smad6 have an inhibitory effect on BMP signaling during osteoblast differentiation by targeting the BMP-responsive Smad1/5/8 complex [ 49 , 54 ]. It has been demonstrated that high extracellular calcium decreased the levels of phosphorylated SMAD1, ERK 1/2, and p38 and that Ca 2+ could bind BMP-2 extracellularly [ 55 , 56 ]. In contrast, low concentrations of extracellular calcium (0.18 mM) enhanced BMP-2-induced osteogenic differentiation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%